Edukacja kulturalna i regionalna instrumentem podtrzymującym tradycję i poczucie ukorzenienia w globalnej rzeczywistości - Kotowicz-Borowy, Irena (Studia Etnologiczne i Antropologiczne, 2014)
Unstable currently communication between generations, migrations and life globalization makes that determining of own identity becomes more difficult.Simultaneously commercialization of cultural heritage along with the development of merket economy may result in a threat to existence of native or regional culture. All the more, regional and cultural education, gaining greater importance, playing the essential role in the „small homelands”, as in the educational environment.Their aim is to restore post-memory, promotion of cultural heritage and using of cultural resources of local communities for the promotion and development of social capital in the region.